2022
DOI: 10.1007/s40544-021-0585-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ultrafine particles from hardfacing coated brake rotors

Abstract: Automotive brake rotors are commonly made from gray cast iron (GCI). During usage, brake rotors are gradually worn off and periodically replaced. Currently, replaced brake rotors are mostly remelted to produce brand-new cast iron products, resulting in a relatively high energy consumption and carbon footprint into the environment. In addition, automotive brakes emit airborne particles. Some of the emitted particles are categorized as ultrafine, which are sized below 100 nm, leading to a series of health and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…The simulation of the PHEV results in a PN saving Despite its wear resistance, the weight analysis showed that the brake disc was subject to a loss of mass. Studies have shown that coating debris enters the environment as wear products [10,44]. The coating wear products may possess a number of hazards to human health [45].…”
Section: Regenerative Brakingmentioning
confidence: 99%
“…The simulation of the PHEV results in a PN saving Despite its wear resistance, the weight analysis showed that the brake disc was subject to a loss of mass. Studies have shown that coating debris enters the environment as wear products [10,44]. The coating wear products may possess a number of hazards to human health [45].…”
Section: Regenerative Brakingmentioning
confidence: 99%
“…Just like brakes, [22][23][24][25][26] the clutch in these experiments exhibits a run-in and a steady state phase. However, contrary to brakes where ultrane particles are predominately generated during the run-in phase, 27 the clutch emits ultrane particles both during run-in and in the steady state, as seen in Fig. 7.…”
Section: Discussionmentioning
confidence: 94%